Health system transformation in Indonesia: Implementation and challenges of six policy pillars - El-Tsana, Ashfiya Vi'aqila; Alvianty, Rizka Ayu; Octaviani, Putri; Syahidah, Raisha; Wasir, Riswandy (Indonesian Journal of Health Science, 2025)
Indonesia’s health system transformation is structured around six strategic pillars: primary care, referral services, system resilience, financing, human resources, and health technology. This study aims to assess the implementation progress and challenges associated with these pillars. A literature review was conducted using national and international databases (Google Scholar and ScienceDirect), focusing on peer-reviewed articles published between 2016 and 2025. Four studies were selected based on inclusion criteria that emphasized relevance to Indonesia’s health system transformation agenda. The review identified key challenges, including limited digital infrastructure, uneven distribution of the health workforce, rigid financing mechanisms, particularly within Public Service Agency (BLU) institutions and weak intersectoral coordination. Many facilities remain unprepared for digital integration, particularly the implementation of Electronic Medical Records (EMR). Although some improvements have been observed, structural barriers continue to hinder the overall progress. Strengthening digital readiness, enhancing workforce capacity, adopting more flexible budgeting mechanisms, and improving coordination, especially through platforms such as SATUSEHAT are recommended as strategic responses. However, this study has several limitations, such as the limited availability of articles that cover all six pillars comprehensively and most of the studies used emphasize legal and administrative aspects rather than specific analysis in the health sector. These limitations limit the generalization of the findings. These findings are expected to inform more adaptive and equitable health policy reforms in Indonesia.